Development of HFCT for partial discharge sensors. (August 2019) - Waldi, E P; Frenzi, AY; Fernandez, R; Darmawan,; Darwison,; Laksono, H D; Aulia,; Novizon,; Hazmi, A; Abral, H; Arief, S; Nawawi, Z; et al.
Abstract: This paper presents partial discharge (PD) measurement techniques using a commercial sensor, High-Frequency Current Transformer (HFCT). An Output signal from HFCT is read by a digital oscilloscope and compared with the reading of convensional that PD detector. When PD occurs, the signals detected using high impedance that has a long time of oscillations and cause the delay of next reading of PD signals. To avoid this issue, the time of oscillations must be reduced by installing a damper which is a resistor connected in parallel between the sensor and the oscilloscope. The result of the measurement shows that the damper has the same reading on peak values as read by the convensional PD detector.